Inhibition of Pro-Inflammatory Microglia with Minocycline Improves Cognitive and Sleep-Wake Dysfunction Under Respiratory Stress in a Sporadic Model for Alzheimer's Disease - Vicente, Mariane C. [UNESP] (2023)
Background: Neuroinflammation in Alzheimer's disease (AD) can occur due to excessive activation of microglia in response to the accumulation of amyloid-β peptide (Aβ). Previously, we demonstrated an increased expression of this peptide in the locus coeruleus (LC) in a sporadic model for AD (streptozotocin, STZ; 2 mg/kg, ICV). We hypothesized that the STZ-AD model exhibits neuroinflammation, and treatment with an inhibitor of microglia (minocycline) can reverse the cognitive, respiratory, sleep, and molecular disorders of this model. Objective: To evaluate the effect of minocycline treatment in STZ model disorders. Methods: We treated control and STZ-treated rats for five days with minocycline (30 mg/kg, IP) and evaluated cognitive performance, chemoreflex response to hypercapnia and hypoxia, and total sleep time. Additionally, quantification of Aβ, microglia analyses, and relative expression of cytokines in the LC were performed. Results: Minocycline treatment improved learning and memory, which was concomitant with a decrease in microglial cell density and re-establishment of morphological changes induced by STZ in the LC region. Minocycline did not reverse the STZ-induced increase in CO2 sensitivity during wakefulness. However, it restored the daytime sleep-wake cycle in STZ-treated animals to the same levels as those observed in control animals. In the LC, levels of A and expression of Il10, Il1b, and Mcp1 mRNA remained unaffected by minocycline, but we found a strong trend of minocycline effect on Tnf- α. Conclusion: Our findings suggest that minocycline effectively reduces microglial recruitment and the inflammatory morphological profile in the LC, while it recovers cognitive performance and restores the sleep-wake pattern impaired by STZ.